Harnessing the regenerative potential of interleukin11 to enhance heart repair - Kwangdeok Shin; Anjelica Rodriguez-Parks; Chanul Kim; Isabella M. Silaban; Yu Xia; Jisheng Sun; Chenyang Dong; Sunduz Keles; Jinhu Wang; Jingli Cao; Junsu Kang (Nature Communications)
Abstract Balancing between regenerative processes and fibrosis is crucial for heart repair, yet strategies regulating this balance remain a barrier to developing therapies. The role of Interleukin 11 (IL11) in heart regeneration remains controversial, as both regenerative and fibrotic functions have been reported. We uncovered that il11a, an Il11 homolog in zebrafish, can trigger robust regenerative programs in zebrafish hearts, including cardiomyocytes proliferation and coronary expansion, even in the absence of injury. Notably, il11a induction in uninjured hearts also activates the quiescent epicardium to produce epicardial progenitor cells, which later differentiate into cardiac fibroblasts. Consequently, prolonged il11a induction indirectly leads to persistent fibroblast emergence, resulting in cardiac fibrosis. While deciphering the regenerative and fibrotic effects of il11a, we found that il11-dependent fibrosis, but not regeneration, is mediated through ERK activity, suggesting to potentially uncouple il11a dual effects on regeneration and fibrosis. To harness the il11a’s regenerative ability, we devised a combinatorial treatment through il11a induction with ERK inhibition. This approach enhances cardiomyocyte proliferation with mitigated fibrosis, achieving a balance between regenerative processes and fibrosis. Thus, we unveil the mechanistic insights into regenerative il11 roles, offering therapeutic avenues to foster cardiac repair without exacerbating fibrosis.